Whether and how does the Crisis-Induced Situation Change e-Leadership in the Public Sector? Evidence from Lithuanian Public Administration - Rita Toleikienė; Irma Rybnikova; Vita Juknevičienė (Transylvanian Review of Administrative Sciences, 2020)
In the course of the pandemic, the remote working and e-leading (leading through information and communication technologies) have also become the usual mode in public administrations, yet research on their consequences for employees in the public sector remains scarce. The aim of this article is to reveal what challenges and tensions emerge in relation to e-leadership in Lithuanian municipal administrations and how the pandemic influences e-leadership and its effects on municipal employees. A qualitative exploratory empirical study based on semi-structured interviews was conducted in a Lithuanian municipal administration before and during the pandemic caused by the COVID-19. It was found that, before the pandemic, e-leadership was mostly initiated by individual supervisors in municipal administrations who encouraged employees to use various e-tools for communication and daily performance of tasks; however, it was poorly supplemented by teleworking. The crisis-induced situation made e-leadership mandatory because of implemented teleworking. It has led to a massive agglomeration of e-leading tasks by supervisors who play the crucial role in instructing employees to use e-tools, gathering and sharing the information, monitoring and reviewing the division of functions and tasks. We also discuss the critical effects on employees, such as multitasking and total availability, resulting from e-leadership and teleworking.